Postpartum Haemorrhage (PPH) & Role of Carbetocin: An Advanced Novel Therapy - Bhalla , Amit (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
To prevent postpartum haemorrhage (PPH), the routine administration of a uterotonic agent like oxytocin is standard practice. Failure of prophylaxis with oxytocin occurs commonly, necessitating the use of further oxytocin or other treatments to maintain haemodynamic stability. Oxytocin has its limitations as it requires cold storage and transport, and in low-resource settings, the cold chain is not commonly available. By modifying the oxytocin molecule, its half-life has been prolonged and its enzymatic degradation reduced. The modified molecule is named carbetocin. Heat-stable carbetocin is a promising alternative to oxytocin, which can overcome the persistent problems with oxytocin quality as it does not require a cold chain for storage and transport.